Noninvasive brain stimulation for behavioural and psychological symptoms of dementia: A systematic review and meta-analysis - Vacas, Sara M.; Stella, Florindo [UNESP]; Loureiro, Julia C.; Simões do Couto, Frederico; Oliveira-Maia, Albino J.; Forlenza, Orestes V. (Wiley, 2019)
Background: Pharmacological and conventional nonpharmacological treatments for behavioural and psychological symptoms of dementia (BPSD) have only modest efficacy. Furthermore, pharmacotherapy carries the risk of important side effects. Noninvasive brain stimulation (repetitive transcranial magnetic stimulation (TMS) or transcranial direct current stimulation (tDCS)) are valuable and safe for cognitive function in Alzheimer disease (AD). However, there have been few studies, and there is no consensus, regarding the use of these techniques to treat BPSD. Methods: We performed a systematic review of the literature and meta-analysis of studies reporting the effect of rTMS or tDCS on BPSD. Results: Seven articles were included: five randomized, controlled clinical trials and two open-label clinical trials. Five studies investigated the effects of rTMS and two the effects of tDCS. Both studies using tDCS reported no evidence of efficacy on BPSD, while two of the three RCTs using rTMS found statistically significant benefits. In an exploratory meta-analysis with four of the RCT studies, we did not find evidence of efficacy of noninvasive brain stimulation techniques, with an overall effect of −0.02 (95% CI = −0.90, 0.94; I2 = 85%). However, when we used only the data from the studies that applied rTMS, we found a positive effect on BPSD, with an overall effect of −0.58 (95% CI = −1.02, −0.14; I2 = 0%). With regards to the adverse effects reported, these were mild and not clinically relevant. Conclusions: Our results establish a tendency for efficacy of rTMS protocols on BPSD, while corroborating their safety and tolerability, suggesting the need for further research.
Keywords: behavioural and psychological symptoms of dementia; neuropsychiatric symptoms of dementia; transcranial direct current stimulation; transcranial magnetic stimulation